Latin America and the Social Contract : Patterns of Social Spending and Taxation - Breceda, Karla; Rigolini, Jamele; Saavedra, Jaime (2012)
This article analyzes the incidence of social spending and taxation by income quintile for seven Latin American countries, the United Kingdom, and the United States. Absolute levels of social spending in Latin America are fairly flat across income quintiles, a pattern similar to that in the United States and differing from the more progressive pattern of spending in the United Kingdom. The structure of taxation in Latin America is also similar to that of the United States. Because of high income inequality in Latin America and the US, the rich bear of most the burden, whereas the United Kingdom taxes the middle class to a greater extent. The analysis suggests that many Latin American countries are trapped in a vicious cycle in which the rich resist the expansion of the welfare state (because they bear most of its tax burden without receiving commensurate benefits), and their opposition to its expansion in turn maintains long-term inequalities.